Stochastic dynamics of structures - El Hami, Abdelkhalak; Radi, Bouchaïb (Mathematical and mechanical engineering set, 2016)
This book is dedicated to the general study of the dynamics of mechanical structures with consideration of uncertainties. The goal is to get the appropriate forms of a part in minimizing a given criterion. In all fields of structural mechanics, the impact of good design of a room is very important to its strength, its life and its use in service. The development of the engineer's art requires considerable effort to constantly improve structural design techniques.